6mer seed toxicity in tumor suppressive microRNAs. Issue 1 (December 2018) - Gao, Quan; Putzbach, William; Murmann, Andrea; Chen, Siquan; Sarshad, Aishe; Peter, Johannes; Bartom, Elizabeth; Hafner, Markus; Peter, Marcus
Abstract Many small-interfering (si)RNAs are toxic to cancer cells through a 6mer seed sequence (positions 2–7 of the guide strand). Here we performed an siRNA screen with all 4096 6mer seeds revealing a preference for guanine in positions 1 and 2 and a high overall G or C content in the seed of the most toxic siRNAs for four tested human and mouse cell lines. Toxicity of these siRNAs stems from targeting survival genes with C-rich 3′UTRs. The master tumor suppressor miRNA miR-34a-5p is toxic through such a G-rich 6mer seed and is upregulated in cells subjected to genotoxic stress. An analysis of all mature miRNAs suggests that during evolution most miRNAs evolved to avoid guanine at the 5′ end of the 6mer seed sequence of the guide strand. In contrast, for certain tumor-suppressive miRNAs the guide strand contains a G-rich toxic 6mer seed, presumably to eliminate cancer cells. Small interfering (siRNAs) can be toxic to cancer cells. Here the authors investigate the toxicity of microRNA in cancer cells by performing a siRNA screen that tests the miRNA activities of an extensive list of miRNAs with different 6mer seed sequences.